Synthesis of low co-ordinate heteroleptic first row transition metal complexes - Churchill, Olivia (2019)
Low co-ordinate transition metal complexes have attracted much interest in recent years due to their high reactivity and unusual magnetic properties. These complexes have often been achieved with the use of bulky m-terphenyl ligands, which have enabled the formation of monomeric and dimeric transition metal complexes. They have also enabled the stabilisation of novel species with unusual bonding modes and oxidation states.